Appraising, processing, and providing access to email in contemporary literary archives. Issue 3 (2nd September 2019) - Schneider, J.; Adams, C.; DeBauche, S.; Echols, R.; McKean, C.; Moran, J.; Waugh, D.
ABSTRACT: The email of contemporary literary ﬁgures is ripe for research by scholars, and of broad interest to the general public, but can also present many challenges to cultural memory institutions that seek to appraise, process and provide access to this rich archival material. This article explores how ﬁve institutions across the United States, United Kingdom and New Zealand are using ePADD, free and open source software developed by Stanford Libraries that incorporates artiﬁcial intelligence and machine learning to help meet these challenges for email in contemporary English‐language literary collections. Authors and institutions represented include British poet Wendy Cope (The British Library), British novelist Ian McEwan (Harry Ransom Center, University of Texas at Austin), British Indian novelist and essayist Salman Rushdie (Emory University), American poet Robert Creeley (Stanford University) and New Zealand poet and critic Ian Wedde (National Library of New Zealand). The use cases are followed by a discussion identifying lessons learned and areas for further research.